Календарно-обрядові пісні Звенигородщиниу фоноколекції Олексія Ошуркевича - Охманюк, В. (Студії мистецтвознавчі, 2007)
In given article is consider calendar-rite folklore of Zvenigorod region (v.Tarasivka, Moryntsi, Kyrylivka), which was included into phonocollection of O. Oshurkevych (records were made in the middle 1980th). On the base of analysis of 20th public songs examples of the spring and the summer cycles author proves existing of eight melotypes – five in spring cycle and three – in summer. On the base of organized analysis he made a conclusion that stated on 80th ÕÕ century best saved were creativities of spring cycle in Zvenigorod region, because they are represented by majority of the quantity of mostoriginal melotypes (five from the eight). Less originality and no-differentiation in genre style he explains by influence of alien for local cultures ambiences.